2003
DOI: 10.1016/s0014-4827(03)00014-4
|View full text |Cite
|
Sign up to set email alerts
|

Id proteins in epithelial cells

Abstract: Id helix-loop-helix (Id HLH) proteins are negative regulators of basic HLH transcription factors. They are expressed during embryonic development and are important for the regulation of cell phenotypes in adults. They participate in the molecular networks controlling cell growth, differentiation, and carcinogenesis, through specific basic HLH and non-basic HLH protein interactions. Recent in vitro and in vivo data implicate Id HLH as important orchestrating proteins of homeostasis in glandular and protective e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 144 publications
2
49
0
1
Order By: Relevance
“…For instance, Crowe et al (13) reported that E2F1, a transcription factor involved in activation of genes associated with the cell cycle, binds to the human telomerase reverse transcriptase promoter and represses its activity. On the contrary, E2F4 and Id2 are positively related to the activity of telomerase (11,12). We find here that intracellular glutathione activates both Id2 and E2F4 and that on the contrary it inactivates E2F1.…”
Section: Modulation Of Glutathione Levels Affects the Rate Of Cell Grmentioning
confidence: 42%
“…For instance, Crowe et al (13) reported that E2F1, a transcription factor involved in activation of genes associated with the cell cycle, binds to the human telomerase reverse transcriptase promoter and represses its activity. On the contrary, E2F4 and Id2 are positively related to the activity of telomerase (11,12). We find here that intracellular glutathione activates both Id2 and E2F4 and that on the contrary it inactivates E2F1.…”
Section: Modulation Of Glutathione Levels Affects the Rate Of Cell Grmentioning
confidence: 42%
“…Ids, a family of four (Id1-Id4) naturally occurring dominantnegative transcription factors that mediate their effects primarily through their highly conserved HLH domain (Benezra et al, 1990;Norton, 2000), are thought to be important regulators of a range of epithelial cell types (Coppe et al, 2003). These proteins have been shown to bind to, and prevent DNA binding by, transcription factors of the bHLH, Pax and ETS families (Benezra et al, 1990;Yates et al, 1999;Roberts et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to growth inhibition by TGF-ß1 has been considered an important step in tumorigenesis and contributes to the development of many tumor types (3,4). Recently, Id1 (inhibitors of DNA binding or differentiation) was revealed to be one of the direct TGF-ß1 target genes (5). Specifically in epithelial cells, Id1 expression can be inhibited through the TGF-ß1-responsive Smad3-activated transcriptional repressor, ATF3, which binds to the ATF/CREB site on the Id promoter, repressing Smad-initiated transcription.…”
Section: Introductionmentioning
confidence: 99%